Narrating Religiosity Through Indonesian Horror Movie: A Semiotic Reading of Qur’anic Verses in Kitab Sijjin & Illiyyin (2025) - Ainun Nabilah; Fejrian Yazdajird Iwanebel (JURNAL AT-TURAS, 2026)
Recent Indonesian horror movies have shown a tendency to feature Islamic elements, ranging from Islamic-themed diction in titles to the appearance of Qur’anic verses in their narratives, which serve as both a representation and a reception of the sacred text. This study aims to analyze how Qur’anic verses can be functionally received and how they represent certain concepts through Roland Barthes’ semiotic reading, Stuart Hall’s Representation, and Ahmad Rafiq’s Reception frameworks. The results of the study show that, first, the representation of people who seek protection from God in Surah Al-Nās is depicted as always receiving His help when facing Satan’s disturbance. Second, the representation of moral opposition between two characters refers to the concepts of al-fujjār and al-abrār in surah Al-Mut}affifīn. Third, the functional reception of the verses of the Qur’an in the form of performative practices through the ritual of ruqyah, namely Surah Āli ‘Imrān verses 26-27, Al-Naml verse 30, Al-Jinn verses 1-6, Al-Ikhlās} verses 1-4, Al-Falaq verses 1-5, and Al-Nās verses 1-6. These findings indicate that films can be a popular medium that enlivens and constructs religious moral messages based on verses from the Qur’an through cinematic narratives, thus opening up further research on the interaction between sacred texts, media, and religious practices in society.